PERAN PEMERINTAH DAERAH TERHADAP PERLINDUNGAN HUTAN ADAT PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 - Daisyta Mega Sari; Akhyaroni Fu'adah (Fakultas Hukum Universitas Gadjah Mada, 2014)
AbstractThe rights of indigenous people have been guaranteed in Article 18(B) paragraph (2) of our constitution, however there are actions that have potentially decrease such right, e.g. the Act of Forestry, which categorizes Community Forest under State Forest. This leads to conflicts between these forests. Subsequently, Constitutional Court issued the Decision of Constitutional Court 35/PUU-X/2012, which distinguishes Community Forest and State Forest. Nonetheless, this decision did not give significant progress to the matter, as it is interpreted as conditionally constitutional. Moreover, in accordance to the Basic Agrarian Law and the Constitution, the Community Forest shall be distinct, in order to recognize the indigenous people’s rights, however this is not properly upheld by the Local Government. There are little number of local regulations that recognizes existence of such right, therefore cooperation between indigenous people and the Local Government shall be made until the existence of such rights are recognized, and prosperity may be reached. IntisariHak-hak masyarakat adat telah terjamin dalam Pasal 18(B) ayat (2) dalam UUD NRI 1945. Tetapi, masih ada tindakan yang dapat mengurangi hak tersebut, e.g. Undang-Undang Kehutanan, yang mengkategorisasikan Hutan Adat dibawah Hutan Negara. Hal ini menimbulkan konflik diantara kedua hutan tersebut. Atas hal ini Mahkamah Konstitusi mengeluarkan putusan 35/PUU-X/2012 yang membedakan Hutan Adat dengan Hutan Negara. Namun, putusan ini tidak memberi kemajuan secara signifikan, dikarenakan putusan tersebut dianggap konstitusional bersyarat. Selain itu, sesuai dengan UUPA dan UUD, Hutan Adat harus dibedakan untuk menjamin hak-hak masyarakat adat, akan tetapi hal ini tidak diimplementasikan dengan baik oleh Pemerintah Daerah. Masih sedikit peraturan daerah yang mengakui adanya hak-hak tersebut. Kerjasama antara masyarakat adat dan Pemerintah Daerah sangat dibutuhkan hingga tercapainya pengakuan hak-hak tersebut, dan kesejahteraan untuk masyarakat adat.